Nationalism in a Transnational Age Irrational Fears and the Strategic Abuse of Nationalist Pride - Jacob, Frank; Schapkow, Carsten (De Gruyter, 2021)
Nationalism was declared to be dead too early. A post-national age was announced, in which transnational alliances like the European Union were supposed to become more important, but we are witnessing the rise of strong forms of nationalism during the early 21st century. This volume shows how nationalist dreams and fears alike determine politics in an age that was supposed to witness a rather peaceful coexistence.